Effect of social skills training program on self- esteem and aggression among children in residential institutions in Port Said City - Soma Ibrahim Ali; Sorayia Ramadan Abdel-Fatah; Amal Sobhy Mahmoud; Sonia Mohamed El- Sayad (Archives of Nursing Practice and Care - Peertechz Publications, 2018)
Background: There is now an abundance of global evidence demonstrating serious developmental and psychological problems associated with placement in residential care which refl ected in the form of poor self-esteem, aggressive behavior, academic failure and later on, personality disorder. Aim: The study aimed to evaluate the effect of social skill training program on self-esteem and aggression among children in residential institutions in Port-Said City. Subjects and Methods: A quasi-experimental research design was used. The present study was carried out at all governmental residential institutions in Port Said city namely, Al-Nessaieya le Tahseen Al- Seha, Dar Alkaserat, Kafalit Al-Yateem, and Apnaa Ramses. The subject of the study compromised 57 children, 36 were males and 21 were females. Three tools were utilized to collect data in this study which are Socio-demographic data questionnaire, Self-esteem inventory scale, and Aggressive behavior scale for children.